#VLADDYDADDY ON TIKTOK: IMAGINED INTIMACY AND MEMETIC PARTICIPATION IN TIMES OF WAR - Divon, Tom; Jaramillo-Dent, Daniela; Gekker, Alex (AoIR Selected Papers of Internet Research, 2023)
#Vladdydaddy is a popular internet meme that emerged during the 2016 elections in the United States on 4chan and Twitter to characterize the perceived submissive behavior of Donald Trump towards Vladimir Putin. The meme re-emerged on TikTok in the days leading to the Russian invasion of Ukraine in February 2022, gaining a new meaning. This paper is part of a larger research project with the objective of identifying and scrutinizing various forms of social media memetic participation in response to human tragedies, such as the Russia-Ukraine war. In this paper we focus on "DM memes" as a creative sub-meme of #Vladdydaddy. Drawing from theories of memetic participation (Milner, 2016) and imagined intimacy (Greenwood & Long, 2011) for the analysis. The findings suggest that the DMing Putin meme emerges as a collective coping mechanism to fulfill an emotional need through the construction of imagined intimacy. The strict censorship laws within Russian borders underscores the significance of exploring seemingly trivial online discursive practices as courageous in a political context that can carry grave consequences offline. In doing so, we bring to the forefront the global community of creators who take a firm stance towards the current political climate in Russia.